An Overview of the Depiction of Women’s Psychological Problems in the Poetry of Professor Dr. Salma Shaheen - Qadir, Shukria (sourcecoder, 2023)
The number of female writers is very less than the male writers in Pashto literature. The main reason for article the restrictions on women in Pashtun society. Nevertheless, Pashtun women have played an important role in promoting of Pashto literature. Although social restrictions were imposed on them, but they got a modern education and raised voice for their rights. There was also a right to freedom of expression. Besides ordinary women, female writers also came forward to achieve the goal. One of them is Dr. Salma Shaheen. She has described many aspect of Pashtun society. In which the issues of Pashtun women have been discussed with great boldness. This article highlights the social and psychological issues of Pashtun women described in Dr. Salma Shaheen's poetry.